PH‐Gated Activation of Gene Transcription and Translation in Biocatalytic Metal–Organic Framework Artificial Cells. Issue 1 (27th October 2020) - Liu, Jian; Guo, Ziyi; Li, Yong; Liang, Jieying; Xue, Jueyi; Xu, Jiangtao; Whitelock, John M.; Xie, Lei; Kong, Biao; Liang, Kang
Abstract : Regulating gene expression is an important goal for the development of artificial cells that have the ability to replicate the functions of living cells. Despite that, it remains a critical challenge to the engineering of artificial cells that can self‐regulate genetic expression in response to the "extracellular" environments. Herein, the gene transcription and translation engineered into metal–organic framework (MOF)‐based artificial cells using extracellular pH as a versatile gate to control green fluorescence protein (GFP) expression is reported for the first time. The results show that the artificial cells can metabolize biological molecules through an engineered multistep process of biocatalytic reactions, and importantly, sense acidic pH in the extracellular environment to initiate gene expression, mimicking natural cells. Moreover, co‐culturing with living cells further prove the adaptive cellular responses in the artificial cells when the target proteins can be produced in response to the change in local cell environments. The versatility of the gene expression regulation mechanism and the sensing of external stimuli by artificial cells supports the goal to bring protocells one step closer to native cells and suggests the potential of the artificial systems in biosensing and therapy applications. Abstract : An advanced artificial cell is constructed using biocatalytic metal–organic framework (MOF) pseudo‐organelles and metal–phenolic network pseudomembrane via interfacial self‐assembly, which is able to sense ambient pH change and produce green fluorescence protein in response. Moreover, co‐culturing the artificial cells with living cells further demonstrates its adaptive cellular responses and shows great promise in future cell therapy applications.